Morphological Aspects Of Hyalinomembrane Disease In Newborn Children - Mirzabekova O. A.; Dadabaeva R. K. (Zien Journals, 2023)
In this scientific study, morphological and morphometric indicators of hyaline membrane disease in premature infants were studied. The material was obtained from the results of clinical-anamnestic analysis of preterm infants at 22-37 weeks and lung tissue. The results show that the immaturity of lung tissue, circulatory disorders and damage to the alveolar and bronchial epithelium play an important role in the development of hyaline membrane disease in the lungs of premature infants. The results of morphometric studies showed that only 1/3 of the lungs of infants born at 22-27 weeks had air in the alveoli, the thickness of the alveolar interstitial tissue, the epithelium of the alveoli was relatively large, and the resulting hyaline membranes were composed of relatively thin fibers. At 28–32 and 33–37 weeks, the dying groups observed an expansion of the area occupied by airborne alveoli in the infant’s lungs, thinning of the interstitial tissue, and thickening of the hyaline membranes compared to the previous group
Keywords: infant; premature birth; lung; alveoli